クルクミン類似体GO-Y022はクルクミンよりも低濃度で圧負荷による心機能低下を抑制した - 川瀬, 裕斗; 森本, 達也; 船本, 雅文; 長谷川, 浩二; 平子, 裕太; 砂川, 陽一; 清水, 聡史; 柴田, 浩行; HANHAO, WU; 清水, 果奈; 刀坂, 泰史 (日本薬理学会年会要旨集, 2022)
Background: We previously reported that natural compound curcumin suppresses cardiomyocyte hypertrophy and the development of heart failure via inhibiting p300 histone acetyltransferase (HAT) activity. In this study, we investigated the effect of curcumin analogue, GO-Y022 on p300-HAT activity, cultured cardiomyocyte hypertrophy and heart failure in vivo.Methods & Results: In vitro HAT assay using recombinant p300-HAT domain showed that GO-Y022 inhibited p300-HAT activity as well as curcumin. Primary cultured cardiomyocytes prepared from neonatal rats were treated with curcumin or GO-Y022 and stimulated with phenylephrine (PE). 1 µM GO-Y022 suppressed the following results to the same extent as 10 µM of curcumin: PE-induced histone acetylation, hypertrophic response gene transcription, and cardiomyocyte hypertrophy. Finally, 8-week-old C57BL/6J male mice were subjected to transverse aortic constriction (TAC) surgery and orally administrated GO-Y022 or curcumin for 8 weeks. Cardiac echography indicated that a low dose of GO-Y022 (1 mg/kg) repressed TAC-induced increase in left ventricular posterior wall dimension and decrease in Fractional shortening to the same extent as 50 mg/kg of curcumin. Conclusion: GO-Y022 may be used for heart failure therapy at a lower dose than curcumin.